microRNA-Based Network and Pathway Analysis for Neuropathic Pain in Rodent Models - Zheng, Yi-Li; Su, Xuan; Chen, Yu-Meng; Guo, Jia-Bao; Song, Ge; Yang, Zheng; Chen, Pei-Jie; Wang, Xue-Qiang (Frontiers in Molecular Biosciences, 2022)
Neuropathic pain (NP) is poorly managed, and in-depth mechanisms of gene transcriptome alterations in NP pathogenesis are not yet fully understood. To determine microRNA-related molecular mechanisms of NP and their transcriptional regulation in NP, PubMed, Embase, Web of Science and CINAHL Complete (EBSCO) were searched from inception to April 2021. Commonly dysregulated miRNAs in NP were assessed. The putative targets of these miRNAs were determined using TargetScan, Funrich, Cytoscape and String database. A total of 133 literatures containing miRNA profiles studies and experimentally verify studies were included. Venn analysis, target gene prediction analysis and functional enrichment analysis indicated several miRNAs (miR-200b-3p, miR-96, miR-182, miR-183, miR-30b, miR-155 and miR-145) and their target genes involved in known relevant pathways for NP. Targets on transient receptor potential channels, voltage-gated sodium channels and voltage-gated calcium channels may be harnessed for pain relief. A further delineation of signal processing and modulation in neuronal ensembles is key to achieving therapeutic success in future studies.